Happy ending of life-threatening upper GI bleeding. (2nd November 2011) - Islam, Quazi Tarikul; Siddiqui, Mahmudur Rahman; Rahman, Md Anisur; Ahmed, Syed Salahuddin
Abstract : Strongyloides stercoralis is an intestinal nematode in humans, and estimated about tens of millions of people are infected worldwide. This parasite is endemic in tropical or temperate and subtropical climates like Bangladesh. The authors report a 33-year-old man who presented with recurrent life-threatening upper gastrointestinal bleeding from gastric infection by S stercoralis.